A review of Malipatilius (Hemiptera: Heteroptera: Rhyparochromidae), with a checklist of Lygaeoidea occurring in the Papuan Subregion - Kondorosy, Előd; Kovács, Szilvia; Schmidt, Péter (Zootaxa, 2024)
The genus Malipatilius Kondorosy, 2013 is redescribed, 8 new species are described (M. batantensis sp. nov., M. bodisjuditae sp. nov., M. horvathi sp. nov., M. macrops sp. nov., M. microps sp. nov., M. minutus sp. nov., M. pilosus sp. nov. and M. szentivanyi sp. nov.) (the authorship is Kondorosy & Schmidt for all species) from the Papuan Subregion. The genus is compared with other genera of Drymini (Rhyparochromidae: Rhyparochrominae) and its species are keyed. Malipatilius forticornis (Gross, 1965) is recorded for the first time from New South Wales (Australia). A checklist of the Lygaeoidea (Hemiptera: Heteroptera) of the Papuan Subregion (New Guinea with surrounding islands) is given, totalling 215 species, 155 of which are endemic, compared with 53 species of Pyrrhocoroidea and 184 species of Coreoidea from this Subregion.